Burden of Mental Morbidities among Health Care Workers in a Tertiary Care Hospital Of West Bengal during Third Wave of COVID-19 Pandemic: A Cross-Sectional Study - Soumi Ghosh; Sourav Bag; Arijit Mondal; Soumit Roy (Perspectives In Medical Research)
Introduction: Healthcare workers (HCWs) are constantly on the frontlines, facing the brunt of the COVID 19 pandemic in their personal, professional, and social lives. This pandemic has also taken a toll on the lives of healthcare workers over the past two years. Facing the stress and burnout since the pandemic has begun, during the third wave of the pandemic, there might be an increase in mental health issues among HCWs in this state. The aim of the study is to assess the magnitude of anxiety and depression during the third wave of COVID-19 pandemic among the healthcare workers in a tertiary care hospital in West Bengal.